2014
DOI: 10.1063/1.4874267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nonlinear optical properties in donor–acceptor materials

Abstract: Time-dependent density functional theory has been used to calculate nonlinear optical (NLO) properties, including the first and second hyperpolarizabilities as well as the two-photon absorption cross-section, for the donor-acceptor molecules p-nitroaniline and dimethylamino nitrostilbene, and for respective materials attached to a gold dimer. The CAMB3LYP, B3LYP, PBE0, and PBE exchange-correlation functionals all had fair but variable performance when compared to higher-level theory and to experiment. The CAMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 70 publications
1
46
0
Order By: Relevance
“…These two methods include different fractions of HF exchange in different solvents, again emphasizing that the exchange energy-be it short or long range-is of critical importance to describe hyperpolarizabilities, 21,22,35 and their dependence on the media. 55,89 Additionally, the largest dependencies on the error are seen for the solvent/gas averages of differences in Table 5. The solvent cavity structure around the target molecule may thus be important to describe hyperpolarizabilities in solution; evidence ‡ Using data at 1 064 nm only (to avoid bias from the dependence of the error on the frequency).…”
Section: Solvent and Frequency Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…These two methods include different fractions of HF exchange in different solvents, again emphasizing that the exchange energy-be it short or long range-is of critical importance to describe hyperpolarizabilities, 21,22,35 and their dependence on the media. 55,89 Additionally, the largest dependencies on the error are seen for the solvent/gas averages of differences in Table 5. The solvent cavity structure around the target molecule may thus be important to describe hyperpolarizabilities in solution; evidence ‡ Using data at 1 064 nm only (to avoid bias from the dependence of the error on the frequency).…”
Section: Solvent and Frequency Effectsmentioning
confidence: 98%
“…Although vibrational contributions to hyperpolarizabilities can be important in some cases, the vibrational contributions to β || in PNA have been estimated to reduce the hyperpolarizability by no more than about 5% at the frequencies considered here. 89,92 On the other hand, the error in the gas phase measurement of β || is reported to be 4%. 85 Furthermore, in ref 55 the methods providing best agreement with the experimental data in Table 4 were also found to agree the most with MP2 hyperpolarizabilities, which can be expected to be reasonably accurate.…”
Section: Solvent and Frequency Effectsmentioning
confidence: 99%
“…The hyperpolarizabilities calculated for these compounds using a variety of methods are summarized in Table 8; the errors are also computed using MP2/6-311+G(d,p) data as reference, which are usually very accurate in gas phase 40,43 (see also discussion in the PNA results section). As can be seen from this Table, To investigate further the cause of this failure of DFT methods in describing the hyperpolarizabilities of 1 and 2, we analyze the charge transfer properties of these compounds, as well as the relationship between β || and ω. Firstly, the difference in density between the ground and excited state are shown in Figure 4.…”
Section: Diagnostic Toolmentioning
confidence: 99%
“…18,[32][33][34][35][36][37][38][39][40][41][42] However, some recent works have also concluded that LC-DFT does not consistently outperform hybrids and GGAs; for example, in Ref. 43, the range-separated CAM-B3LYP provides the best results in some solvents, but the standard hybrid B3LYP is better in others. These two seemingly contradictory observations may be reconciled by considering the fact that the optimal range separation parameter ω in LC-DFT has been shown to be strongly system dependent.…”
Section: Introductionmentioning
confidence: 99%
“…DMANS is a typical example of the so-called push-pull chromophors, where an electron donating group is coupled to an electron accepting group through a p-conjugated bridge, in this case, stilbene. Owing to its large hyperpolarizability, DMANS has been considered as a potential material for nonlinear optics applications [13,14]. DMANS is structurally flexible with five possible torsion angles ( Fig.…”
Section: Introductionmentioning
confidence: 99%